2004
DOI: 10.1039/b313253f
|View full text |Cite
|
Sign up to set email alerts
|

Polysubstituted phthalocyanines by nucleophilic substitution reactions on hexadecafluorophthalocyanines

Abstract: Nucleophilic substitution reactions on hexadecafluorophthalocyaninato zinc(II) with a variety of O, N, C, and S nucleophiles led to narrowly defined mixtures of polysubstituted phthalocyanines, some of which are completely inaccessible by classical phthalonitrile condensation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…214c, 232 The distribution of the reaction products was monitored by mass spectrometry. Based on these data, it was found that, as expected, aromatic nucleophilic substitution of the fluorine atoms results in a broad distribution of reaction products rather than formation of individual complexes, although in some cases narrowly defined mixtures of polysubstituted products were observed.…”
mentioning
confidence: 99%
“…214c, 232 The distribution of the reaction products was monitored by mass spectrometry. Based on these data, it was found that, as expected, aromatic nucleophilic substitution of the fluorine atoms results in a broad distribution of reaction products rather than formation of individual complexes, although in some cases narrowly defined mixtures of polysubstituted products were observed.…”
mentioning
confidence: 99%
“…[265][266][267] This research group showed that the C-F bonds in zinc hexadecafluorophthalocyanine 90 could be replaced by a variety of carbon-, oxygen-, sulfur-, and nitrogen-centered nucleophillic reagents to form mixtures of asymmetric phthalocyanines 91 with various degrees of substitution. The reaction product distribution was studied by mass spectrometry.…”
Section: Simple Aromatic Electrophilic or Nucleophilic Reactionsmentioning
confidence: 99%
“…If diamines were used as the nucleophiles, the reaction products are mixtures of cyclic substituted phthalocyanines, binuclear and trinuclear (amine bridged) compounds, or mixtures of both of these types depending on the structures of the diamines used. [265][266][267] Scheme 30. Formation of asymmetric phthalocyanines using partial substitution of the peripheral C-F bonds in hexadecafluorophthalocyanine.…”
Section: Simple Aromatic Electrophilic or Nucleophilic Reactionsmentioning
confidence: 99%
See 2 more Smart Citations